Islamic Financial Bank Performance in Indonesia and Malaysia - Sarwenda Biduri; Wiwit Hariyanto; Sigit Hermawan; Endra Wahyu Nindiyah (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
The increasing popularity of Islamic banks with the opening of various Islamic banks, both independent and as one of the long-established subsidiaries of conventional banks, seems to show that the banking industry, which applies Sharia principles in every business step, promises profitable business expansion opportunities. The purpose of this study is to compare the financial performance of Islamic commercial banks that were established in Indonesia and Malaysia in the 2016 – 2018 period using general financial ratios, namely the ratio of CAR, ROA, FDR and Total Asset Turnover. The research sample was taken by purposive sampling. The data obtained were analyzed by descriptive statistical methods to see the overall performance of banks both within and between countries, then the independent sample t test was used to see the significance of the differences in the performance of each type of banking industry in each country, both in Indonesia and Malaysia. This study shows that the financial performance of Islamic commercial banks in Indonesia and Malaysia has significant differences.